Sistem Informasi Pendukung Keputusan Pengadaan Armada Baru Pada PT. Jaya Sampurna Makmur Bekasi Berbasis Web Mengunakan Metode Weighted Product (Jurnal Sistem Informasi dan Ilmu Komputer, 2023)
Companies in making a decision require good consideration, therefore we need a system that helps provide information from good data processing so that it becomes the basis for decision making. This analysis aims to create a decision support system that can help the company to provide an overview of the decision to procure a new fleet that the company wants to buy.This decision support information system is implemented using the Hypertext Preprocessor (PHP) programming language and MySsql as the database application so that the desired features are created and neatly stored in operating the information system.This decision support information system also uses the Weighted Product method which is used to assist in decision making in determining the procurement of new fleets.The end result of this decision support information system is to combine a programming language with the Weighted Product method which can be used for decision making in determining which new fleet to buy, where the calculations are based on several predetermined criteria so that their use is on target.